Використання вейвлет-аналізу для дослідження часових рядів якісних параметрів роботи станції дефекосатурації цукрового заводу - Заїка, В. І.; Кишенько, В. Д. (Видавництво Львівської політехніки, 2011)
The opportunities of application of wavelet analysis to study the time series of historical data and comparing results with analysis using Fourier transforms.
Keywords: wavelet analysis; fourier transform; time series